2014
DOI: 10.1002/jcph.359
|View full text |Cite
|
Sign up to set email alerts
|

Targeted adsorption of molecules in the colon with the novel adsorbent‐based Medicinal Product, DAV132: A proof of concept study in healthy subjects

Abstract: During antibiotic treatments, active residuals reaching the colon profoundly affect the bacterial flora resulting in the emergence of resistance. To prevent these effects, we developed an enteric-coated formulated activated-charcoal based product, DAV132, meant to deliver its adsorbent to the ileum and neutralize antibiotic residues in the proximal colon. In a randomized, control, crossover study, the plasma pharmacokinetics of the probe drugs amoxicillin (500 mg) absorbed in the proximal intestine, and sulfap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 26 publications
4
47
0
Order By: Relevance
“…in a mouse model of gut colonization [85]. In human volunteers, these products have recently shown that they can selectively adsorb drug compounds in the proximal colon, without interfering with drug absorption in the proximal small intestine [86]. Co-administration of ciprofloxacin and activated charcoal inserted in zinc balls (which release the coal only in the colon) also showed a significant decrease in fecal concentrations of ciprofloxacin in rats and no effect on PK/PD plasma ciprofloxacin parameters [87].…”
Section: Measures To Limit the Impact Of Fq On Microbiotamentioning
confidence: 97%
See 1 more Smart Citation
“…in a mouse model of gut colonization [85]. In human volunteers, these products have recently shown that they can selectively adsorb drug compounds in the proximal colon, without interfering with drug absorption in the proximal small intestine [86]. Co-administration of ciprofloxacin and activated charcoal inserted in zinc balls (which release the coal only in the colon) also showed a significant decrease in fecal concentrations of ciprofloxacin in rats and no effect on PK/PD plasma ciprofloxacin parameters [87].…”
Section: Measures To Limit the Impact Of Fq On Microbiotamentioning
confidence: 97%
“…Yet, before this occurs, we hope to see more successful ways of limiting the impact of antibiotics on microbiota, and not only concerning FQ, such as charcoal-based coating techniques to limit the impact of antibiotics in the proximal colon. The proof of concept has been made and clinical studies have recently begun [85,86]. Closer down the line, FMT may also be an alternative treatment for subjects colonized with multi resistant organisms and suffering recurring infections.…”
Section: Future Perspectivementioning
confidence: 97%
“…43 This adsorbent product irreversibly captures antibiotics in the intestine whilst hopefully avoiding interruption of antibiotic absorption. DAV132 has been examined in a proof-of-concept study involving 18 healthy subjects.…”
Section: Difficile Infection Prophylaxismentioning
confidence: 99%
“…In vitro human gut model and in vivo hamster models also have positive findings but clinical efficacy data are awaited. 43 …”
Section: Difficile Infection Prophylaxismentioning
confidence: 99%
“…Another study has demonstrated the potentiality of non-enzymatic intra-intestinal inactivation of residual ciprofloxacin by colon-targeted zinc-pectinate beads loaded with activated charcoal [13,14]. This approach has recently been applied with success in a phase I clinical trial [15]. This system is however not selective to the antibiotics and nonspecific adsorption of other molecules can occur interfering with major physiological processes.…”
Section: Introductionmentioning
confidence: 97%